Studi kelayakan pemanfaatan fly ash dan bottom ash menjadi paving blok di PLTU Banten 3 Lontar - Zakaria Tatan; Anita Dyah Juniarti (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2020)
Banten 3 Lontar Power Plant is a steam generating electric power plant that use coal as the main fuel. Banten 3 Lontar power plant is located in Tangerang with the production capacity are 315 MW which is distributed to consumers in the Jakarta and Tangerang areas. Accordingly, the electricity production process, PLTU Banten 3 Lontar also produces B3 waste of fly ash and bottom ash. Referring to Government Regulation No. 101 of 2014 concerning Management of Hazardous and Toxic Waste, Banten 3 Lontar PLTU routinely transferred bottom ash and fly ash to other companies that have permission to process bottom ash from Ministry of Environment and Forestry. The bottom ash expenditure process requires a fairly high cost. After conducting chemical testing, paving blocks derived from FABA material with a mixture of aggregate and cement, the chemical content is still eligible to be used as a paving block product by TCLP test, No. AAS.LHP.V.2019.0698 dated May 6, 2019, where the parameters are below the quality standard. Based on the compressive strength test on a sample of paving blocks with a curing time of 28 days, producing a strength of 262.4 kg / cm2, it was declared appropriate in accordance with certificate No. 02968 / ALBAAM, 12 August 2019. As for the economic study, the use of fly ash and bottom ash into paving blocks is feasible to be implemented. because the Return on Investment (ROI) is 13.92% and the Payback Period is 7.2 months.